SOSIALISASI PEMBUATAN SABUN CUCI PIRING UNTUK MEMBANGUN KREATIVITAS IBU RUMAH TANGGA DI RT 008 DESA TANGKIT - Tamsir; Ririn Angraini; Mulia Indah Maharani; Mirop Sahara (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This community service activity aims to enhance the creativity and economic independence of housewives in RT 008, Tangkit Village, through training on how to independently produce liquid dishwashing soap. The program was initiated based on the lack of knowledge and practical skills among housewives in creating household cleaning products, despite their high interest in learning simple and economical production techniques. This activity employed a descriptive library research approach by collecting theoretical references related to raw materials, their functions, and formulation steps, which were later used as the basis for educational activities. The implementation consisted of interviews with community representatives, coordination with local authorities, and direct demonstrations involving participants. A total of 25 housewives participated in the hands-on workshop, where they learned the functions of key materials such as SLES, NaCl, Sodium Sulfate, EDTA, Ambithol, fragrances, and colorants, as well as the proper mixing techniques. The practice produced several bottles of liquid dishwashing soap with stable texture and clarity after overnight settling. The results indicate that participants were enthusiastic, able to follow the process well, and showed increased motivation to practice the production at home. Some participants even expressed interest in developing the product as a potential home-based business. Overall, the program succeeded in increasing knowledge, skills, and entrepreneurial awareness among housewives in RT 008 Tangkit Village.